Differential expression and prognostic role of selected genes in colorectal cancer patients - Pitule, Pavel; Vyčítal, Ondřej; Brůha, Jan; Novák, Petr; Hošek, Petr; Třeška, Vladislav; Hlavatá, Ivona; Souček, Pavel; Králíčková, Milena; Liška, Václav (Anticancer research, 2013)
AIM: Colorectal cancer (CRC) is one of the most common malignant diseases. The aim of our study was to describe the expression status of 12 selected candidate genes, by comparing paired samples of healthy colon mucosa and tumour tissues and to correlate obtained data with clinical and pathological features, with the goal of revealing associations for individual gene expressions and tumour behaviour. MATERIALS AND METHODS: Samples from 53 patients with CRC were analyzed. Patients were divided into two groups based on the presence or absence of distant metastases at the time of primary tumour surgery. Expression levels were assessed by quantitative real-time polymerase chain reaction. RESULTS: We found changes in the expression of 10 out of 12 analyzed genes. Four genes were significantly up-regulated in tumour tissues: leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5; p<0.001), collagen triple helix repeat containing 1 (CTHRC1; p<0.001), visinin-like 1 (VSNL1; p<0.001) and versican (VCAN; p=0.001). Six genes were down-regulated: destrin (DSTN; p=0.004), mesoderm induction early response 1, family member 3 (MIER3; p<0.001), acyl-CoA synthetase long-chain family member 5 (ACSL5; p=0.002), mitogen-activated protein kinase 1/ERK (MAPK1; p<0.001), claudin 23 (CLDN23; p<0.001) and solute carrier family 26 (sulfate transporter), member 2 (SLC26A2; p<0.001). We recorded longer overall survival (OS) in the group of patients with higher expression of VSNL1 (p=0.032). Patients with more pronounced down-regulation of CLDN23 had shorter OS (p=0.045). In the group of patients without distant metastases, longer OS and disease-free interval (DFI) were found for patients with higher SLC26A2 expression in tumour tissues (p=0.036 and p=0.011, respectively). In the same group, lower expression of VSNL1 in healthy tissue corresponded to a longer DFI (p=0.020), smaller decrease of SLC26A2 and ACSL5 meant longer DFI (p=0.041 and p=0.040, respectively), as did greater increase of LGR5 expression (p=0.026). CONCLUSION: We identified differences in the expression of 10 genes in colorectal cancer tissue compared to healthy colon mucosa, and found prognostic significance for these changes which could be used for the development of a disease risk scoring system.
Keywords: kolon; kolorektální nádory; Palliative Care; Female; paliativní péče; Lymphatic Metastasis; lymfatické metastázy; ženské pohlaví; Colorectal Neoplasms; adjuvantní chemoterapie; Colon; lidé; Neoplasm Grading; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; následné studie; míra přežití; prognóza; RNA, Messenger; stupeň nádoru; Follow-Up Studies; Male; Reverse Transcriptase Polymerase Chain Reaction; nádorové biomarkery; Aged; Chemotherapy, Adjuvant; Prognosis; Survival Rate; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; Middle Aged; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans